2023
DOI: 10.1186/s12891-023-06569-6
|View full text |Cite
|
Sign up to set email alerts
|

Age, pelvic incidence, facet joint angle and pedicle-facet angle as correlative factors for isthmic spondylolisthesis: a retrospective case control study

Abstract: Background Isthmic spondylolisthesis (IS) is a common clinical disease with a high incidence rate. However, most current researches explain the clear pathogenesis from a single perspective. The aim of our study was to explore the relationships between multiple parameters in patients and find the potential risk factors of this disease. Methods Our study retrospectively included 115 patients who were diagnosed with isthmic spondylolisthesis and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The result of our study was the same as this of Park et al This may be more in line with reality because, as mentioned earlier, facet angle and facet joint hypertrophy were the main in uencing factors of FJV, and patients with isthmic lumbar spondylolisthesis tend to have a larger facet angle [ 20 ], whereas facet angle tend to be smaller in degenerative lumbar spondylolisthesis, because the development of degenerative lumbar spondylolisthesis was associated with smaller facet angle [ 21 , 22 ]. Interestingly, in our study, isthmic lumbar spondylolisthesis had the highest probability of facet joint hypertrophy, and degenerative lumbar spondylolisthesis had the highest probability of high-grade facet joint degeneration (Weishaupt grade ≥2), that is, patients with degenerative lumbar spondylolisthesis had more severe subarticular bone erosion osteophytes, which may be related to the different biomechanical changes resulting from the two different structural alterations, while the speci c reasons need more and more in-depth studies (Table 5).…”
Section: Discussionsupporting
confidence: 87%
“…The result of our study was the same as this of Park et al This may be more in line with reality because, as mentioned earlier, facet angle and facet joint hypertrophy were the main in uencing factors of FJV, and patients with isthmic lumbar spondylolisthesis tend to have a larger facet angle [ 20 ], whereas facet angle tend to be smaller in degenerative lumbar spondylolisthesis, because the development of degenerative lumbar spondylolisthesis was associated with smaller facet angle [ 21 , 22 ]. Interestingly, in our study, isthmic lumbar spondylolisthesis had the highest probability of facet joint hypertrophy, and degenerative lumbar spondylolisthesis had the highest probability of high-grade facet joint degeneration (Weishaupt grade ≥2), that is, patients with degenerative lumbar spondylolisthesis had more severe subarticular bone erosion osteophytes, which may be related to the different biomechanical changes resulting from the two different structural alterations, while the speci c reasons need more and more in-depth studies (Table 5).…”
Section: Discussionsupporting
confidence: 87%
“…It is considered one of the major causes of low back pain among the elderly and is a major cause of spinal canal stenosis associated with low back and leg pain [16]. Kong et al [17] reported that the mean value of age was significantly higher in individuals with spondylolisthesis and that there was a positive correlation between age and spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Andrade et al [44] conducted an epidemiologic systematic review of 15 published observational studies analyzing any association between IS and clinical of the pars interarticularis [28]. Even though many factors have been proposed for the etiology of DS and IS, the exact triggers for the onset and progression of spondylolisthesis are still unclear [29][30][31]. Lumbar DS could cause low back pain (LBP) and leg symptoms (neurogenic claudication) due to the slippage and concomitant lumbar spinal stenosis, respectively [27].…”
Section: Does Radiology Correlate With Clinical Findings?mentioning
confidence: 99%
“…A recent meta-analysis reported that demographic and radiological factors including female sex, body mass index, menopause, early IVDD, sagittal facet joint orientation, joint laxity, high pelvic incidence, presence of spondylolisthesis at L4-L5 level, increased L4 or L5 vertebral angle, increased lumbar I axis sacral I distance, increased lumbar lordotic angle, and having more than 25% slippage were associated with the symptoms of DS [31,[45][46][47][49][50][51][52][53][54][55]. It has been shown that age, pelvic incidence, facet joint angle, and pedicle facet angle were associated with IS [29]. To overcome those confounders, our patients were matched in terms of age, sex, lumbar lordosis, pelvic incidence, subtype (DS or IS) and Meyerding grade of their spondylolisthesis.…”
Section: Confoundersmentioning
confidence: 99%